مصادر تمويل موازنات وحدات الحكم المحلي ( سورية – مصر ) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
تعمل وحدات الإدارة المحلية على رسم سياساتها الاقتصادية والاجتماعية والتنموية المتوافقة مع مصالح ومطالب مجتمعاتها المحلية، ولكي تتمكن تلك الوحدات من ممارسة وظائفها وتحقيق أهداف سياساتها المعتمدة، فإنها تحتاج إلى إدارة مواردها المالية بكفاءة تجنباً للهدر واتقاءً للعجز المالي الذي يؤثر سلباً على وظائفها وحتى استمراريتها. انطلاقاً مما سبق يحظى التمويل المحلي بأهمية متزايدة في دراسات الإدارة المحلية. يهدف هذا البحث لدراسة تمويل وحدات الادارة المحلية في كل من سورية ومصر, حيث سنتناول بالبحث تعريف كل من المشرعين السوري والمصري لهذه الوحدات ونظرته لها, ثم سنبحث في ايرادات هذه الوحدات وعلى كافة مستوياتها بشكل تفصيلي, مبينين لمصادر هذا التمويل ومفصلين لكافة التشريعات والقوانين ذات الصلة به, وتقدم الدراسة بعض التوصيات لتعزيز ايرادات الوحدات المحلية وتنظيم شؤونها المالية والقانونية بشكل دقيق وفعال, مما يتيح لهذه الوحدات قيامها بمهامها بفعالية وعلى اكمل وجه Local administration units work to formulate their economic, social and development policies that are compatible with the interests and demands of their communities, In order for these units to function and achieve their policy objectives, they need to manage their financial resources efficiently in order to avoid waste and prevent financial deficits that adversely affect their functions and sustainability. As a result, local finance is increasingly important in local management studies The aim of this study is to study the financing of the local administration units in Syria and Egypt, We will discuss the definition of the Syrian and Egyptian legislators for these units and their consideration, Then we will examine the revenues of these units at all levels in detail, indicating the sources of this funding and details of all relevant legislations and laws, The study provides some recommendations to enhance the revenues of local units and to organize their financial and legal affairs in a precise and effective manner, allowing these units to carry out their tasks effectively and in full Policies.